Program and Abstract book of the Fourth International Persian Congress of Acarology - Masoud Hakimitabar; Alireza Sazmand (Eds.) (Persian Journal of Acarology)
The Fourth International Persian Congress of Acarology was held on 28-30 July 2022 in Mashhad, Iran.